Exploring TRIM proteins’ role in antiviral defense against influenza A virus and respiratory coronaviruses - Wei, Ying; Song, Junzhu; Zhang, Jingyu; Chen, Songbiao; Yu, Zuhua; He, Lei; Chen, Jian (Frontiers in Cellular and Infection Microbiology, 2024)
Numerous tripartite motif (TRIM) proteins, identified as E3 ubiquitin ligases, participate in various viral infections through ubiquitylation, ISGylation, and SUMOylation processes. Respiratory viruses, particularly influenza A virus (IAV) and respiratory coronaviruses (CoVs), have severely threatened public health with high morbidity and mortality, causing incalculable losses. Research on the regulation of TRIM proteins in respiratory virus infections is crucial for disease prevention and control. This review introduces TRIM proteins, summarizes recent discoveries regarding their roles and molecular mechanisms in IAV and CoVs infections, discusses current research gaps, and explores potential future trends in this rapidly developing field. It aims to enhance understanding of virus–host interactions and inform the development of new molecularly targeted therapies.